Molecular variability of Czech plum pox virus isolates - Navrátil, M; Simonová, V; Fialová, R; Válová, P (Acta virologica, 1998)
Seventy-two Czech plum pox virus (PPV) isolates from different hosts were tested by double-antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA). In addition, the coat protein mobility and the RsaI restriction fragment length polymorphism (RFLP) pattern of reverse transcription-polymerase chain reaction-(RT-PCR) amplified coat protein (CP) gene fragment of the isolates were analysed. Both PPV-D and PPV-M serotypes were found in the Czech Republic. The results obtained by these different methods were in accord with exception of a few cases probably caused by mutation or recombination.
Keywords: Serotyping; monoklonální protilátky; virus šarky švestky; Antibodies, Monoclonal; polymerázová řetězová reakce s reverzní transkripcí; Blotting, Western; ELISA; Enzyme-Linked Immunosorbent Assay; polymorfismus délky restrikčních fragmentů; Česká republika; western blotting; Plum Pox Virus; Polymorphism, Restriction Fragment Length; Reverse Transcriptase Polymerase Chain Reaction; nemoci rostlin; Plant Diseases; Czech Republic; sérotypizace